Morphological priming effects on children’s spelling - Rosa, Joao Manuel (2015)
Previous research has suggested that children in the early grades of primary school do not have much awareness of morphemes. In this study, a priming paradigm was used to try to detect early signs of morphological representation of stems through a spelling task presented to Portuguese children (N = 805; age range 6–9 years). Primes shared the stem with the targets and contained well-articulated, stressed vowels; the stems of the target words and pseudo-words contained nonstressed schwa vowels, which typically result in spelling difficulties. If priming proved effective, the well-articulated vowels in the prime should result in an improvement in the spelling of the schwa vowels. Primes were presented in two conditions: in only-oral or in oral-plus-written form. Effectiveness of priming was assessed by comparison with a no-priming condition. For both words and pseudowords, there was a significant interaction between priming effects and grade. No priming effects were detected in 6- and 7-year-old children; oral-plus-written priming produced higher rates of correct vowel spelling for 8- and 9-year-olds; only-oral priming was effective in improving the vowel spelling of 9-year-olds. Thus older children can use morphological information under priming conditions when the prime and the target are not phonologically transparent but there is no evidence to suggest that younger children do so.